2017
DOI: 10.1097/md.0000000000008492
|View full text |Cite|
|
Sign up to set email alerts
|

A multicenter, open-label, phase III study of Abcertin in Gaucher disease

Abstract: Background:Gaucher disease (GD) is caused by a deficiency in the lysosomal enzyme glucocerebrosidase. Enzyme replacement therapy (ERT) is recommended for clinical improvement.Methods:The efficacy and safety of a new imiglucerase, Abcertin, were assessed in 7 Egyptian patients with treatment-naïve type 1 GD. Each patient was administered a biweekly 60 U/kg dose of Abcertin for 6 months. The primary endpoint was the change in hemoglobin concentration. The secondary endpoints were changes from baseline in platele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…For example, in Pompe disease, the level of expression of mannose receptors on skeletal muscle cells is low, necessitating high doses of erT to achieve a therapeutic effect 202 . Numerous developments are being studied to address such limitations, with a focus on enzyme modifications that enable better access of enzymes to their receptors and on nanomaterials that enable safe and efficient delivery of enzymes via intra-cerebroventricular/intrathecal administration 10,46,200,203 .…”
Section: Wwwnaturecom/nrdmentioning
confidence: 99%
“…For example, in Pompe disease, the level of expression of mannose receptors on skeletal muscle cells is low, necessitating high doses of erT to achieve a therapeutic effect 202 . Numerous developments are being studied to address such limitations, with a focus on enzyme modifications that enable better access of enzymes to their receptors and on nanomaterials that enable safe and efficient delivery of enzymes via intra-cerebroventricular/intrathecal administration 10,46,200,203 .…”
Section: Wwwnaturecom/nrdmentioning
confidence: 99%
“…Abcertin was initially approved in South Korea in 2012 via a national pathway that permitted the submission of phase 3 data after approval, and outside of approval pathways for biosimilars and other orphan drugs. It was approved based on the results of three clinical studies: a 5‐day, double‐blind, placebo‐controlled Phase 1 dose‐escalation study conducted in 24 healthy volunteers (NCT01881633); a 24‐week prospective, Phase 2, open‐label switch‐over study in one adult and four children/adolescents with confirmed GD type 1 previously treated with Cerezyme; and a post‐approval, 24‐week, Phase 3 trial in 7 treatment‐naïve children with GD type 1 . Studies providing a direct comparison to the RP, Cerezyme, and physicochemical, immunological, or structural data have not been presented.…”
Section: Gaucher Disease (Gd) a Rare Disease Examplementioning
confidence: 99%
“…Authors of the Phase 2 study initially referred to Abcertin as a “biosimilar” for Cerezyme . Although they have since corrected their claim in an erratum to their initial publication, confusion could persist regarding the precise nature of Abcertin .…”
Section: Gaucher Disease (Gd) a Rare Disease Examplementioning
confidence: 99%
“…In the article, “A multicenter, open-label, phase III study of Abcertin in Gaucher disease”, [ 1 ] which appears in Volume 96, Issue 45 of Medicine , Table 1 contained incorrect information and the correct table appears below.…”
mentioning
confidence: 99%